Could the Identification of Skin Lesions Be Beneficial for the Differential Diagnosis of Viral Meningitis? - Agata Marszałek; Weronika Górska; Artur Łukawski; Carlo Bieńkowski; Maria Pokorska-Śpiewak (Zoonotic Diseases, 2025)
Viral infections may vary from mild to severe, manifesting with a wide range of symptoms, including skin lesions, influenza-like symptoms, or meningitis/meningoencephalitis signs. Viruses that cause both skin lesions and meningitis comprise, e.g., Enteroviruses (EVs) and Herpes viruses (HV). EVs are responsible for approximately 90% of viral meningitis cases. They occur frequently among children under 3 years of age and are characterized by various types of rash. HV infections are responsible for up to 18% of viral meningitis, mostly among adults or older children. Most patients with viral meningitis recover entirely. However, the rates of serious complications and mortality may be as high as 74% and 10%, respectively, for particularly vulnerable neonatal or immunocompromised patients. Patients that present signs of encephalitis and/or are suspected to have HSV/VZV infection require immediate implementation of empiric acyclovir therapy before receiving the polymerase chain reaction (PCR) test results. The clinical picture of viral meningitis may differ depending on the virus, including the presence of both meningeal signs and skin lesions. Therefore, early identification of the etiological factor is necessary for early and proper treatment implementation. It is crucial to accurately differentiate between the causative agents, and this work focuses on answering the question of how skin lesions can assist in achieving a better and faster diagnosis. The aim of this review was to analyze the characteristics of skin lesions in the course of meningitis caused by various viral species. This can be helpful for physicians in the diagnostic process and subsequent treatment.